Propylene glycol, a component of electronic cigarette liquid, damages epithelial cells in human small airways - Moegi Komura; Tadashi Sato; Hitomi Yoshikawa; Naoko Arano Nitta; Yohei Suzuki; Kengo Koike; Yuzo Kodama; Kuniaki Seyama; Kazuhisa Takahashi (Respiratory Research, 2022)
Abstract Background Electronic cigarettes (e-cigarettes) are used worldwide as a substitute for conventional cigarettes. Although they are primarily intended to support smoking cessation, e-cigarettes have been identified as a gateway to smoking habits for young people. Multiple recent reports have described the health effects of inhaling e-cigarettes. E-cigarette liquid (e-liquid) is mainly composed of propylene glycol (PG) and glycerol (Gly), and the aerosol generated by these devices primarily contains these two components. Thus, this study aimed to evaluate the effects of PG and Gly on human small airway epithelial cells (SAECs). Methods SAECs were exposed to PG or Gly, and cell proliferation, cell viability, lactate dehydrogenase (LDH) release, DNA damage, cell cycle, and apoptosis were evaluated. Additionally, SAECs derived from chronic obstructive pulmonary disease (COPD) patients (COPD-SAECs) were investigated. Results Exposure of SAECs to PG significantly inhibited proliferation (1%, PG, p = 0.021; 2–4% PG, p < 0.0001) and decreased cell viability (1–4% PG, p < 0.0001) in a concentration-dependent manner. Gly elicited similar effects but to a reduced degree as compared to the same concentration of PG. PG also increased LDH release in a concentration-dependent manner (3% PG, p = 0.0055; 4% PG, p < 0.0001), whereas Gly did not show a significant effect on LDH release. SAECs exposed to 4% PG contained more cells that were positive for phosphorylated histone H2AX (p < 0.0001), a marker of DNA damage, and an increased proportion of cells in the G1 phase (p < 0.0001) and increased p21 expression (p = 0.0005). Moreover, caspase 3/7-activated cells and cleaved poly (ADP-ribose) polymerase 1 expression were increased in SAECs exposed to 4% PG (p = 0.0054). Furthermore, comparing COPD-SAECs to SAECs without COPD in PG exposure, cell proliferation, cell viability, DNA damage and apoptosis were significantly greater in COPD-SAECs. Conclusion PG damaged SAECs more than Gly. In addition, COPD-SAECs were more susceptible to PG than SAECs without COPD. Usage of e-cigarettes may be harmful to the respiratory system, especially in patients with COPD.